Meningkatkan Volume Penjualan Serta Mengoptimalkan Literasi Digital : Studi Kasus Happy Family Mart - Nur Fitriana; Ghina Adenia; Ranaya Aura Difa; Nadisa Lailatul Rahmi; Putri Ayuni Giawa; Krisvina Mariana; Nindia Putri (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
In today's digital era, digital literacy has become one of the important aspects that influences the success of retail businesses. This community service aims to analyze the digital literacy of business owners and the technological competencies of employees at Happy Family Mart, as well as how these two factors can increase sales volume. Through this community service, it is expected that solutions can be found for the problems faced, such as inadequate digital capabilities of business owners, manual financial recording systems, underutilization of Ipos software, minimal digital promotion, and low employee understanding in technology usage. The results of this community service are expected to provide useful recommendations for business owners and employees in optimizing retail information systems and increasing sales volume.